(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Cultural identity is considered one of the most important issues raised in our contemporary world due to the rapid changes that contemporary societies are going through, Conflicts have swept the world and modern technologies have become a threat to existing social entities. Moreover, customs, traditions and social norms are some of the significant dimensions that constitute the cultural identity any community – the Armenian community. The Armenian Community resided in Egypt for more than a hundred years since they arrived in Egypt from Armenia during WWI. No matter how longs these years are, they still carry their cultural identity: The Armenian culture, art, literature, customs and traditions. In such context, this study looks at the documentary films which have been produced to monitor the Armenian social, political, religious and cultural lives in Egypt. Documentary films is one of the most influential means because a single shot is stronger than a million of words, especially in this period of time, which depends heavily on the visual reference that tells history and documents the human interaction existing in these communities. The study questions were how much the lives of the Armenians are expressed in the documentary films selected and whether the treatment of documentary films came true about the life of Armenians.